Fruits of knowledge - Carlander, Fennia; Lothigius, Karin (2011)
This report is a literature review that aims to describe marketing contexts for mango production in Kenya. The institutional conditions in the country are not well developed for marketing purposes, which causes many difficulties and problems for the society. In Kenya most mango producers are poor small-scale farmers with limited resources. Mango is a perishable commodity and to keep its value and quality it is essential to have the opportunity to sell the mangos in the right time. Inefficient and undeveloped infrastructure and marketing systems hinders the mangos to reach the market in time though, which causes large losses of produce.